1992
DOI: 10.1039/c39920000604
|View full text |Cite
|
Sign up to set email alerts
|

C60embedded in γ-cyclodextrin: a water-soluble fullerene

Abstract: A water-soluble complex of c60 is formed on refluxing a solution of y-cyclodextrin with solid c60; the lifetime of the triplet excited state of c60 in the complex is 83 ps in an oxygen free solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
267
1
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 474 publications
(281 citation statements)
references
References 11 publications
9
267
1
4
Order By: Relevance
“…␥-Cyclodextrin has been shown to form non-covalent supramolecular 2:1 host-guest complex with fullerene, which in aqueous solution, exists in a monomeric state, possibly due to the formation of hydrogen bonds [18,19]. Benesasson et al demonstrated that C 60 is extensively incorporated into phosphatidylcholine liposomes, but the degree of aggregation depends mainly on the relative concentration of C 60 to phosphatidylcholine [20].…”
Section: Introductionmentioning
confidence: 99%
“…␥-Cyclodextrin has been shown to form non-covalent supramolecular 2:1 host-guest complex with fullerene, which in aqueous solution, exists in a monomeric state, possibly due to the formation of hydrogen bonds [18,19]. Benesasson et al demonstrated that C 60 is extensively incorporated into phosphatidylcholine liposomes, but the degree of aggregation depends mainly on the relative concentration of C 60 to phosphatidylcholine [20].…”
Section: Introductionmentioning
confidence: 99%
“…At present time, the highest concentration of C 60 achieved in the FWS is ∼ 1.4 g/l [5][6][7]. It should be noted that the formation of similar fullerene C 60 structures in different organic solvents was not observed [2][3][4] showing an important influence of water on their formation and existence [5][6][7].The discovery of single-walled carbon nanotubes [8,9] have provided the opportunity to study their mechanical, optical and electronic properties [10,11]. Specifically, their electronic characteristics are predicted to vary depending upon the nanotube symmetry and diameter, thus giving either metallic or semiconducting behaviour [1].…”
mentioning
confidence: 88%
“…In particular, for biomedical testing, water-soluble forms of fullerenes are undoubtedly of great interest. Poor solubility in water of fullerenes and their derivatives limits biological and medical studies, even though there were reports on successfully prepared micro-and macro-colloidal particle solutions in organic solvents or in water [2][3][4][5][6][7]. In particular, G.V.…”
mentioning
confidence: 99%
“…To make a water-soluble fullerene was one of the great challenges in fullerene chemistry and scientific interest in the potential applications of these fascinating molecules [3] in the biochemical, biophysical and biological field. There were some introductions to make fullerene derivatives that were soluble in aqueous condition [4][5][6][7][8][9][10][11][12]. While a number of fullerene derivatives have been prepared for such a purpose, most of them have been of only poor aqueous solubility, the results of that have limited application in chemical reactions.…”
Section: Introductionmentioning
confidence: 99%